Ad-hoc, mobile, and wireless network : 12th International Conference, ADHOC-NOW 2013, Wrocław, Poland, July 8-10, 2013. Proceedings - Gȩbala, Maciej; Klonowski, Marek; Cichon, Jacek (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed proceedings of the 12th International Conference on Ad-hoc, Mobile, and Wireless Networks, ADHOC-NOW 2013, held in Wroclaw, Poland, in July 2013. The 27 revised full papers presented were carefully reviewed and selected from 56 submissions. The papers address such diverse topics as routing, rumor spreading, reliability, topology control, security aspects, and the impact of mobility. Some of the papers contain precise analytical results while other ones are devoted to solving specific practical problems of implementation and deployment.